Enhancing Teacher Beliefs through an Inquiry-Based Professional Development Program - Tammy R. McKeown; Lisa M. Abrams; Patricia W. Slattum; Suzanne V. Kirk (Journal of Education in Science, Environment and Health)
Inquiry-based instructional approaches are an effective means to actively engage students with science content and skills. This article examines the effects of an ongoing professional development program on middle and high school teachers’ efficacy beliefs, confidence to teach research concepts and skills, and science content knowledge. Professional development activities included participation in a week long summer academy, designing and implementing inquiry-based lessons within the classroom, examining and reflecting upon practices, and documenting ways in which instruction was modified. Teacher beliefs were assessed at three time points, pre- post- and six months following the summer academy. Results indicate significant gains in reported teaching efficacy, confidence, and content knowledge from pre- to post-test. These gains were maintained at the six month follow-up. Findings across the three different time points suggest that participation in the professional development program strongly influenced participants’ fundamental beliefs about their capacity to provide effective instruction in ways that are closely connected to the features of inquiry-based instruction.